Association of breakfast consumption with objectively measured and self-reported physical activity, sedentary time and physical fitness in European adolescents: the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study. Issue 10 (11th September 2013) - Cuenca-García, Magdalena; Ruiz, Jonatan R; Ortega, Francisco B; Labayen, Idoia; González-Gross, Marcela; Moreno, Luis A; Gomez-Martinez, Sonia; Ciarapica, Donatella; Hallström, Lena; Wästlund, Acki; Molnar, Dénes; Gottrand, Frederic; et al.
Abstract Objective To examine the association of breakfast consumption with objectively measured and self-reported physical activity, sedentary time and physical fitness. Design The HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Cross-Sectional Study. Breakfast consumption was assessed by two non-consecutive 24 h recalls and by a 'Food Choices and Preferences' questionnaire. Physical activity, sedentary time and physical fitness components (cardiorespiratory fitness, muscular fitness and speed/agility) were measured and self-reported. Socio-economic status was assessed by questionnaire. Setting Ten European cities. Subjects Adolescents (n 2148; aged 12·5–17·5 years). Results Breakfast consumption was not associated with measured or self-reported physical activity. However, 24 h recall breakfast consumption was related to measured sedentary time in males and females; although results were not confirmed when using other methods to assess breakfast patterns or sedentary time. Breakfast consumption was not related to muscular fitness and speed/agility in males and females. However, male breakfast consumers had higher cardiorespiratory fitness compared with occasional breakfast consumers and breakfast skippers, while no differences were observed in females. Overall, results were consistent using different methods to assess breakfast consumption or cardiorespiratory fitness (all P ≤ 0·005). In addition, both male and female breakfast skippers (assessed by 24 h recall) were less likely to have high measured cardiorespiratory fitness compared with breakfast consumers (OR = 0·33; 95 % CI 0·18, 0·59 and OR = 0·56; 95 %CI 0·32, 0·98, respectively). Results persisted across methods. Conclusions Skipping breakfast does not seem to be related to physical activity, sedentary time or muscular fitness and speed/agility as physical fitness components in European adolescents; yet it is associated with both measured and self-reported cardiorespiratory fitness, which extends previous findings.